A review on the therapeutic potential and safety profile of juniperus communis linn. - SOURAVH BAIS; NILESH J PATEL (International Journal of Pharma and Bio Sciences, 2018)
Juniperus communisis an evergreen shrub or a small tree indigenous to Europe, South Asia and North America. It is widely distributed throughout the northern hemisphere. The plant belongs to the genus juniperus of the Cypress family (cupressaceae). Medicinal plants have historically proven their value as a source of molecules with therapeutic potential, and nowadays still represent an important pool for the identification of novel drug leads. In the past decades, pharmaceutical industry focused mainly on libraries of synthetic compounds as drug discovery source. They are comparably easy to produce and resupply, and demonstrate good compatibility with established high throughput screening (HTS) platforms. This plant is used traditionally in the treatment of various diseases and disorders like anti- inflammatory, anti-diarrhoeal, astringent, menstrual irregularities and some abdominal disorders. In the last few years, this plant has been selected for various research activities. This plant contains various chemical constituents like α-pnene, β- pinene, Apigenin, Sabinine, β-sitosterol, campesterol, limonene, Amentoflavone, Quinic acid, Isocupressic acid, communic acid, deoxypodophyllotoxin, imbricatolic acid, and many others. So why it was reported for various activities like Anticancer, Hepatoprotective, Antifungal activity, Antioxidant, Anti diabetic activity, Antibacterial, Anti Inflammatory activity, Anti-microbial activity, Anticataleptic activity, Antimalarial activity, Antihypercholectroetic activity, Neuroprotective, Anti-arthritic activity and Anti mycobacterial activity. The aim of the present review is to compile its existing research with special reference to its toxicity and biological activity because one major asset of medicinal plant-based drug discovery is the existence or ethno pharmacological information providing hints for compounds therapeutically effective in humans.